Hindi hindu histories : Caste, ayurveda, travel, and communism in early twentieth century India - Gupta, Charu (New Delhi : Permanent Black, 2024)
What did everyday Hinduism in India look like a hundred years ago? Were its practices more varied and less politically curtailed than now? Hindi Hindu Histories provides illuminating historical accounts of Hindu life through individual actors, autobiographical narratives, and genres in the Hindi print-public culture of early twentieth-century North India. It focuses on four fascinating figures: a successful woman doctor in the Indigenous medical regime, a globe-trotting Hindu ascetic who opposed Gandhi, an anticaste campaigner who spoke for sexual equality, and a Hindu communist who envisioned an egalitarian utopia in the world of labor. These public intellectuals harbored vernacular dreams of freedom and Hindi-Hindu nationhood through their vantage points of caste, Ayurveda, travel, and communism. Opening up a vast and under-explored Hindi archive, this book presents a dynamic spectacle of a plural Hindi-Hindu universe of facets that coexisted, challenged each other, and comprised an idea of Hinduness far more inclusive than anything conceivable in the present moment.
Keywords: Hinduism -- History -- 20th century -- India; Hindus -- Biography -- India; History / Asia / South / India